CONTESTATION OF MODERATE ISLAMIC DISCOURSE IN NU.OR.ID AND MUHAMMADIYAH.OR.ID WEBSITES - Trifita, Amjad; Choirul Arif, Moch.; Zuhriyah, Luluk Fikri (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2023)
This study intends to investigate how moderate Islam is contested on the websites muhammadiyah.or.id and nu.or.id. This study uses Norman Fairclough’s Critical Discourse Analysis approach as a sort of content analysis research. The findings of this study demonstrate that, in the first place, the discourse of moderate Islam in NU media is presented under the slogan “Globalizing Moderate Islam,” while in Muhammadiyah media, the discourse of moderate Islam is presented in relation to ”he accomplishments in seven different areas, including economy, education, morality, social issues, da'wah, nationality, and gender. Second, the discourse process used to portray moderate Islam is examined in terms of textual, social, and sociocultural praxis dimensions. This analysis reveals the various ways that moderate Islam is interpreted as well as the motivations behind such interpretations.